The efficacy of the constitutional organization of the Iraqi freedom to choose his personal status in the Iraqi constitution - Ali, Muthana; Adil, Musadaq (Journal of Legal Sciences, 2022)
We concluded that the issue of freedom in general is one of the important issues of the constitutional legislator, so he was keen to include it in the introduction and content of his texts, because the society suffered from scourge and injustice  And tyranny by the rulers and the ruled made freedom at the mercy of their fatwas. The international and Arab declarations stipulated the necessity of giving public freedoms without racial or national discrimination, but rather for all humanity. It has arranged consequences for those who failed to abide by the conventions, encouraging them to urge national legislators to stipulate public freedoms in Their constitutions, including our desired freedom here, is the freedom of the Iraqi. The constitutions under study clearly stipulated them, and the other varied between referral in vague forms and referral to a religious authority to link it to it.  Multiple laws for all Lebanese and for all segments to choose, according to their religious and spiritual affiliations, their personal status, such as marriage, divorce, ordination, inheritance, and other matters.  As for the Egyptian constitutional legislator, it referred the issue of personal status, according to the 2014 constitution, to regulate it to Al-Azhar, because the Egyptian legislator linked freedom of personal status to religion, and the one responsible for all religious affairs is Al-Azhar Al-Sharif with the statement of the constitution. As for the Iraqi legislator, its texts varied in the old time in  His constitution in 1925 clearly and explicitly stipulated the principle of freedom of personal status, which is considered the first building block for its emergence in the Iraqi constitutional custom. This freedom disappeared under the following constitutions. Rather, this freedom was arbitrarily arbitrarily in the hands of a dictatorial authority that brought together the three authorities. Until the change came in 2003, it  Our desired freedom was breathed by the decision of the Governing Council to abolish the personal status law and to work according to sects, but it did not see the light because it was objected by (Bremer) and it was revoked.  Their personal status according to religion, sect and choice, but he referred the subject of its regulation to the law, and the law has not yet looked into the matter of organizing it, which made it an ink on the  Paper and reflected negatively on the unity of the Iraqi fabric, forcing individuals not to review the personal status courts because of the violation of the law because of their affiliation. There are many evidences we brought in the search for the dire and devastating effects of families because of the silence of the law sometimes and at other times because of the lack of organization of the personal conditions of Iraqis in line with their aspirations and religious affiliations          But the text alone is not sufficient unless it is surrounded by a legal sanction. The Federal Supreme Court moves in order to protect rights and public freedoms, so it was surrounded by general and private guarantees to protect the freedom of personal status from banners on it.